ANALISIS KELAYAKAN FINANSIAL DAN EKONOMI USAHA DEPOT AIR MINUM DI KOTA SINTANG - Emilia Dewiwati Pelipa; Yunita Astikawati (Jurnal Pendidikan Ekonomi (JURKAMI), 2021)
Analysis in opening a business is an important element in order to prevent possible losses in the future. In the city of Sintang, the DAM business already has a large market share. However, a large market share is not necessarily accompanied by good business financial management, especially when opening a business. Therefore, it is necessary to analyze the financial and economic feasibility, especially for DAM business. Quantitative research methods were carried out in this study. The population is 109 DAM businesses. The sample uses purposive sampling. The results of the financial feasibility analysis with the criteria of NPV, IRR, PI, and DPP, all financial aspects indicate that the DAM business is feasible to run. The results of the analysis show the NPV of Rp. 4,563,694.26. > 0, IRR 9.02% > DR 6 %, PI 1.84. The DAM business is economically profitable, and the return on business capital can be achieved in the First year of the DAM business